A critical study on the abuse of the housemaids in Malaysia / Dorine Patrick…[et al.] - Patrick, Dorine; Golingai, Debra Lyn; M Karangkas, Iry; Othman, Norfaraliyana; Mihat, Siti Norihan (2011)
In Malaysia, the cases of maid abuse have been on the rise recently, thus, our study will be based on 'A CRITICAL STUDY ON THE ABUSE OF THE HOUSEMAIDS IN MALAYSIA' and the area that we will be focusing on is in criminal law. This study aimed to critically examine and analyze on the existing law in relation to maid abuse in Malaysia and to suggest an appropriate solution to deal with the flaws in the Malaysian law. This research adopts qualitative type of research which covers interview with the expert in criminal law, internet research and a library based research. In Malaysia, there are a number of statutes, which have the provisions on this issue. They are however, vary slightly from one statute to the other as each ofthe statutes is meant for specific needs and purposes, the statutes that will be involved in this research are Employment Act 1955( Act 265) , The Malaysian Penal Code (Act 574) and Federal Constitution. This study hopes to provide for better understanding by prolTIoting the knowledge with regards to the action that will be taken to those involving in maid abuse; the research serves to recommend best solution for the issue of maid abuse. Not only that, it also can create awareness and it is also can prevent the rise ofthe maid abuse cases in Malaysia because people will have better law after the law is amended.